2016
DOI: 10.1159/000443831
|View full text |Cite
|
Sign up to set email alerts
|

The ADAPAR Birth Cohort Study: Food Allergy Results at Five Years and New Insights

Abstract: Background: Although food allergy (FA) is often a transient condition during childhood, when and in whom FA will resolve can be affected by many factors. In this study, we analyzed the data at 5 years on 33 children diagnosed with FA in the ADAPAR (Adana Pediatric Allergy Research) birth cohort study in southern Turkey. Methods: Thirty-three infants detected as having FA at the end of their first year in the ADAPAR study were assessed every 6 months until the age of 5 years. Each follow-up included a clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 19 publications
0
8
0
2
Order By: Relevance
“…[12] In studies conducted in our country, Turkey, the findings showed that the prevalence of food allergy is 0.8% in 6-9 years in the Black Sea region and 2.4% in the first year of life in Adana. [13,14] Although the number of cases was limited in our study, the median age of the patients was first year of life. This result supports the studies on this subject.…”
Section: Discussionmentioning
confidence: 91%
“…[12] In studies conducted in our country, Turkey, the findings showed that the prevalence of food allergy is 0.8% in 6-9 years in the Black Sea region and 2.4% in the first year of life in Adana. [13,14] Although the number of cases was limited in our study, the median age of the patients was first year of life. This result supports the studies on this subject.…”
Section: Discussionmentioning
confidence: 91%
“…The risk of developing IgE sensitization to cow’s milk has been associated with the duration of breastfeeding and isolated doses of formula feeding in hospital, especially after caesarian delivery [41]. Most children with food allergy develop tolerance, as shown for cow’s milk (17/20) and hen’s eggs (14/17), by the age of 2 years [42]. Risk factors for a persisting allergy to cow’s milk or wheat include having a history of anaphylaxis and high food allergen-specific IgE levels [43, 44].…”
Section: Improving the Diagnosis And Treatment Of Food Allergymentioning
confidence: 99%
“…Milk allergy is the most common FA in children. Milk allergy resolves in approximately 80% of patients by the age of 5 years, but other studies have shown that 19% of them resolve at the age of 4 years and 79% by the age of 16 years [1,10,14] . Similar findings have been observed for egg allergy [15] .…”
Section: The Course Of Natural Tolerancementioning
confidence: 99%